2017
DOI: 10.1177/0021955x17732305
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic performances of silicone foams for sound absorption

Abstract: The aim of this study is the investigation of the link between the elaboration process, the microstructure and the acoustic behaviour of silicone foams obtained using a two-component silicone. Different parameters are varied such as the ratio of components, the addition of a thinning agent and the curing temperature, with the objective of understanding the influence of each parameter in the foam's acoustic absorption. The microstructure is analysed using SEM and acoustic properties are measured. Two non-acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…First impressions of the foam are usually lightweight, energy‐saving, and low cost. In fact, the capability of foams includes various advantages in terms of thermal insulation, [ 1, 2 ] sound barrier, [ 3 ] energy absorption, [ 4 ] and specific mechanical properties. [ 5 ] Nowadays, polymer foams, as the most commonly used foam products, are widely used as building and construction materials, automotive parts, medical equipment, packaging, and upholstery.…”
Section: Introductionmentioning
confidence: 99%
“…First impressions of the foam are usually lightweight, energy‐saving, and low cost. In fact, the capability of foams includes various advantages in terms of thermal insulation, [ 1, 2 ] sound barrier, [ 3 ] energy absorption, [ 4 ] and specific mechanical properties. [ 5 ] Nowadays, polymer foams, as the most commonly used foam products, are widely used as building and construction materials, automotive parts, medical equipment, packaging, and upholstery.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the dip in absorption coefficient recorded between 1000 Hz and 2000 Hz was suspected to be due to an increase in the imaginary part of the impedance. However, at frequencies beyond 3000 Hz, the wavelength became close in magnitude to the foam thickness, leading to higher energy losses and increased absorption as a result of greater interaction between the incident sound waves and the internal structure of the foams [ 76 ]. At about 4000 Hz, it was observed that the sound absorption coefficients recorded for the foams were directly related to their characteristic acoustic impedance ( Figure 7 b).…”
Section: Resultsmentioning
confidence: 99%
“…Each of the tests was repeated three times to obtain consistent and representative results. Average and standard deviation were then computed from the readings [ 76 ]. While microstructural and non-acoustic properties of polymer composites foams do not depend on the size of the sample, sound absorption coefficient and surface impedance mainly depend on the sample thickness [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…3(a). [56][57][58] Those porous materials usually present excellent sound absorption properties in the middle and high frequencies but inherently show much weaker sound dissipation in the lower-frequency range because the thickness of the absorber is limited by the quarter working wavelength, making it difficult to achieve effective absorption of lowfrequency sound waves in a limited space. 59 In previous works, efforts have been devoted to modulating the pore size and increasing the mesh rate, which ensures the absorption peak shis toward the lower frequency band, [59][60][61] but this achievement was rather limited.…”
Section: Acoustic Metamaterials Based On Porous Mediamentioning
confidence: 99%